2015
DOI: 10.1007/s00167-015-3669-6
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative treatment and return to play after complete proximal adductor avulsion in high-performance athletes

Abstract: Case series, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 25 publications
(60 reference statements)
1
31
0
Order By: Relevance
“…The persistent aim of therapy remains to enhance muscle healing and to limit scar formation. Recently, several new injection methods were reported to shorten the recovery time after muscle strain injuries [4][5][6][7][8][9][10]. The injection of local anesthetics, Calf Blood Copmpound (CFC) and Homeo pathic Drug (Tr14), or platelet-rich plasma (PRP), was reported most frequently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The persistent aim of therapy remains to enhance muscle healing and to limit scar formation. Recently, several new injection methods were reported to shorten the recovery time after muscle strain injuries [4][5][6][7][8][9][10]. The injection of local anesthetics, Calf Blood Copmpound (CFC) and Homeo pathic Drug (Tr14), or platelet-rich plasma (PRP), was reported most frequently.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies revealed that Tr14 inhibits the production of pro-inflammatory cytokines like TNF-α and IL-1β [18]. Although it was reported that athletes were successfully treated in practice [9,10], only limited scientific evidence can be found in the literature to support the general use of these agents in the treatment of muscle injuries. The exact mechanism of action of Calf Blood Copmpound (CFC) and Tr14 in the process of muscle healing is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst conservative management programmes have resulted in favourable outcomes, the scarcity of injury and variation in reported protocols precludes consensus on optimal rehabilitation. The criterion-based rehabilitation programme presented in this case followed the principles of progressive mechanical loading in tenopathology (Cook & Docking, 2015;Galloway, Lalley, & Shearn, 2013;Kjaer, 2014) and examples from other conservatively managed tendon avulsion cases in professional football (Fysentzou, 2016;Gamradt et al, 2009;Maciel et al, 2015;Ueblacker, English, & Mueller-Wohlfahrt, 2016). It is conceded that management principles utilised in this case derive heavily from published tendinopathy management approaches (Cook & Docking, 2015;Galloway, Lalley, & Shearn, 2013;Kjaer, 2014), which may not be fully appropriate in cases of tendon avulsion.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for structural healing of the avulsed tendon is considered to exist with conservative management, as demonstrated in cases of lower limb tendon avulsion in professional football (Gamradt et al, 2009;Ueblacker et al, 2016). However, this was demonstrated at 12 weeks post-injury via MRI, but not at six weeks (Ueblacker et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation